Effect of male parental care on reproductive success of burying beetles, nicrophorus vespilloides - Musa, Sharmin (Dhaka University Journal of Biological Sciences, 2011)
The burying beetles, Nicrophorus vespilloides (Coleoptera: Silphidae) show elaborate biparental care. They utilize a carcass as food of their own and to feed their offspring. Male parental care is important for both before and after the larvae hatch. But it is still not clear why male parents stay with the brood after the larvae hatch and provide care. The main objective of the study was to test whether male parents gain any future benefit from providing care that means access to carcass. Present investigation suggested previous parental care experience did not improve offspring fitness of future clutches. The offspring survival traits like number, average weight and development time showed no variation between clutches of experienced and inexperienced male parents. Key words: Parental care; Reproductive success; Burying beetles DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8960 DUJBS 2010; 19(2): 165-170